Does aerobic exercise induced-analgesia occur through hormone and inflammatory cytokine-mediated mechanisms in primary dysmenorrhea?. (February 2019) - Kannan, Priya; Cheung, Kwok-Kuen; Lau, Benson Wui-Man
Abstract: The popular accepted explanation for the pathogenesis of primary dysmenorrhea is elevated levels of uterine prostaglandins. Aetiological studies report that production of prostaglandins is controlled by the sex hormone progesterone, with prostaglandins and progesterone displaying an inverse relationship (i.e. increased progesterone levels reduce prostaglandin levels). Pro-inflammatory cytokines (interleukin-6 [IL-6] and tumor necrosis factor-alpha [TNF-α]) are also implicated in the pathogenesis of primary dysmenorrhea. High-intensity aerobic exercise is effective for decreasing pain quality and intensity in women with primary dysmenorrhea. However, why and how aerobic exercise is effective for treatment of primary dysmenorrhea remain unclear. Our preliminary non-randomized controlled pilot study to examine the effects of high-intensity aerobic exercise on progesterone, prostaglandin metabolite (13, 14-dihydro-15-keto-prostaglandin F2 alpha (KDPGF2α ), TNF-α, and pain intensity found increases in progesterone and decreases in KDPGF2α, TNF-α, and pain intensity following high-intensity aerobic exercise relative to no exercise. Given these promising preliminary findings, as well as what is known about the pathogenesis of primary dysmenorrhea, we propose the following scientific hypothesis: high-intensity aerobic exercise utilizes hormone (progesterone) and inflammatory cytokine-mediated mechanisms to reduce the pain associated with primary dysmenorrhea.